Field science in the age of online learning: Dynamic instruction of techniques to assess soil physical properties - Hinckley, Eve-Lyn S.; Fendorf, Scott (Frontiers in Education, 2022)
Soil physical properties, such as soil texture, color, bulk density, and porosity are important determinants of water flow (e.g., infiltration and drainage), biogeochemical cycling, and plant community composition. In addition, they reflect the environment in which the soil developed, giving insight into climate, mineralogy, and land cover. While many soil assessments require sophisticated laboratory equipment, some can be made simply by a trained individual, requiring only practice and reference materials. For students in environmental fields, it is particularly important and empowering to learn how to make informed soil observations that provide insights from the soil pedon to the landscape and that can be done within the field setting. Drawing on updated pedagogical approaches, including active learning, small group collaboration, and metacognitive exercises, this paper presents a course module for teaching soil texture and color analysis in the field that can be modified for students from secondary through graduate school. The combination of asynchronous, pre-course readings and assessment; synchronous, in-class instruction, hands-on practice, and application activities; and post-class reflection give students the opportunity to build a strong foundation for making soil observations. This course module is suitable for both in-person and remote learning modalities and can be adapted to a number of course topics across environmental disciplines. Ultimately, the goal is to provide students with exciting, hands-on training that inspires them to learn more about soils regardless of the learning platform.